Fibrinogen and factor XIII - Weisel, John (Henry Stewart Talks, 2007)
Fibrinogen and factor XIII, Structure, Biosynthesis, Fibrin polymerization, Crosslinking, Clot mechanical properties, Interactions with other proteins, Fibrinolysis, Platelet aggregation, Dysfibrinogenemias and variants, Evolution